Diagnostic Testing of Learning Difficulties and Remedial Education Intervention for Improving Teaching and Learning in Primary Classes in Sri Lanka - Vithanapathirana, M.V. (My University, 2013)
The study was conducted by the National Education Research and Evaluation Center (NEREC) of the Faculty of Education, University of Colombo. Objectives were: Capacity building of teacher educators to develop a diagnostic instrument to identify learning difficulties of grade 4 students; Facilitate collaborative action toward identified student learning difficulties through remedial interventions at school level This study is unique as it is the first national scale collaborative action research carried out with the collaboration of all teacher education providers in the country. This paper presents the action research conducted by the NEREC with twenty research teams from eighteen teacher education provider institutions. This article mainly focuses on the overall project, its objectives, theoretical background of main concepts, methodological framework and knowledge generated through action research cycles and lessons learned by the entire team. This program comprising identification of learning difficulties and remedial interventions at the primary level of schooling in Sri Lanka is envisioned meeting this urgent systemic need.